The Role of Epoxyeicosatrienoic Acids in Cardiac Remodeling - Lai, Jinsheng; Chen, Chen (Frontiers in Physiology, 2021)
Epoxyeicosatrienoic acids (EETs) are metabolites of arachidonic acid by cytochrome P450 (CYP) epoxygenases, which include four regioisomers, 5,6-EET, 8,9-EET, 11,12-EET, and 14,15-EET. Each of them possess beneficial effects against inflammation, fibrosis and apoptosis, which could combat cardiovascular diseases. Numerous studies have demonstrated that elevation of EETs by overexpression of CYP2J2, inhibition of sEH, or treatment with EET analogs showed protective effects in various cardiovascular diseases, including hypertension, myocardial infarction, as well as heart failure. As is known to all, cardiac remodeling is the major pathogenesis of the cardiovascular diseases. This review will begin with the introduction of EETs and its protective effects in cardiovascular diseases. Following, the roles of EETs in cardiac remodeling, with a particular emphasis on myocardial hypertrophy, apoptosis, fibrosis, inflammation and angiogenesis will be summarized. Finally, it is suggested that upregulation of EETs is a potential therapeutic strategy for cardiovascular diseases. The EETs-related drug development against cardiac remodeling is also discussed, including the overexpression of CYP2J2, inhibition of sEH, as well as the analogs of EET.